Institutional model of state response to profit-motivated crimes in the higher education sector - Стефанов, Д.С (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2024)
The article aims to develop a comprehensive institutional model for the state’s response to mercenary (self-serving) crimes in Ukraine’s higher-education sector, ensuring effective criminal-legal countermeasures, financial oversight, and prevention of academic corruption under current law. In the narrow, criminal-legal sense, mercenary crimes are intentional encroachments motivated by personal gain, expressly criminalized by the Criminal Code; in the broad, social-legal sense, they encompass any abuses that harm public finances or undermine the integrity of the educational process. Core components of the proposed model include the Ministry of Education, Science and Higher Education; the National Anti-Corruption Commission (NACP); the National Anti-Corruption Bureau of Ukraine (NABU); the State Bureau of Investigation (SBI); the prosecutor’s office; and internal compliance departments within higher-education institutions (HEIs). Empirical data from 2023 show that NABU and SBI referred 30 cases against university officials to court, yet only 27 % of HEI compliance officers had the resources for their own inspections and 38 % of university anti-corruption programs remained purely formal. Key obstacles include conflicts of interest among university management, a lack of truly autonomous internal investigations, limited transparency of disciplinary proceedings, and uneven judicial practice. To address these shortcomings, the article proposes creating independent supervisory boards within HEIs empowered to initiate and oversee internal investigations; mandating digital transparency of all HEI budget operations and publication of integrity-commission decisions; and integrating financial-monitoring (BEB) and NACP analytical platforms into a single digital system under the coordination of the Ministry of Education and Science. A methodological triangulation—normative review of the Law “On Operational and Investigative Activities” and the Criminal Procedure Code; content analysis of 49 court decisions (2021–2024); and case studies of three high-profile NABU and SBI investigations—revealed procedural delays in NSRD authorizations, broken data-custody chains, uncertified software, and poor coordination between operational and investigative units. These factors create high latency of offenses and reduce serious mercenary crimes to disciplinary infractions. Strengthening internal oversight, enforcing digital transparency, and improving inter-agency cooperation are therefore essential to ensure the inevitability of criminal liability and safeguard the integrity of Ukraine’s higher-education sector. Keywords: profit-motivated crimes; higher education; anti-corruption policy; institutional model; NABU; NACP; internal audit; operative-search activity; pre-trial investigation.

У статті досліджується інституційна модель державного реагування на корисливі злочини у сфері вищої освіти України станом на травень 2024 р. Метою статті є розроблення цілісної моделі, здатної забезпечити належну кримінально-правову протидію, фінансовий контроль і превенцію академічної корупції в межах чинного нормативного поля. У вузькому кримінально-правовому вимірі корисливі злочини визначено як умисні посягання з корисливим мотивом, що безпосередньо передбачені нормами Кримінального кодексу; у широкому соціально-правовому сенсі — усі зловживання, які завдають шкоди публічним фінансам та доброчесності освітнього процесу. Інституційна модель включає: Міністерство освіти і науки (МОН), Національне агентство з питань забезпечення якості вищої освіти (НАЗЯВО), Національне агентство з питань запобігання корупції (НАЗК), Національне антикорупційне бюро (НАБУ), Державне бюро розслідувань (ДБР), органи прокуратури та внутрішні підрозділи закладів вищої освіти (ЗВО). Емпіричні дані за 2023 р. засвідчили, що НАБУ та ДБР скерували до суду 30 справ проти посадовців університетів, однак лише 27 % внутрішніх уповноважених ЗВО мали ресурси для власних перевірок, а 38 % антикорупційних програм залишаються формальними. Основними проблемами визначено: конфлікт інтересів керівництва, відсутність автономних внутрішніх розслідувань, обмежену публічність дисциплінарних матеріалів та м’яку судову практику. Запропоновано такі заходи: Створення незалежних наглядових рад при ЗВО з правом ініціювати службові розслідування; Впровадження обов’язкової цифрової прозорості бюджетних операцій та обов’язкового оприлюднення рішень комісій з доброчесності; Інтеграція аналітичних платформ БЕБ і НАЗК у єдиний цифровий майданчик під координацією МОН. Проблеми документування корисливих злочинів у ЗВО досліджено трьома доповнювальними методами:– Нормативний аналіз Закону «Про оперативно-розшукову діяльність» і КПК, який виявив затримки з санкціонуванням НСРД і нечіткі правила роботи з цифровими доказами, що позбавляє оперативників «вікна можливостей» для фіксації злочину;– Контент-аналіз 49 судових рішень (2021–2024 рр.), що показав найчастіше відхилення матеріалів НСРД і електронних бухгалтерських баз ЗВО через порушений ланцюг зберігання даних та використання несертифікованого ПЗ;– Кейс-стаді трьох резонансних проваджень НАБУ та ДБР, які засвідчили, що навіть за наявності агентурних напрацювань розслідування гальмується через брак експрес-економічних експертиз і несинхронізованість дій оперативних та слідчих підрозділів. Сукупність цих чинників формує високу латентність правопорушень і сприяє їх зведенню до дисциплінарних порушень, що підриває невідворотність кримінальної відповідальності у сфері вищої освіти. Дотримання запропонованих рекомендацій дозволить створити більш ефективну систему протидії та запобігання корисливим злочинам у вищих навчальних закладах. Ключові слова: корисливі злочини, вища освіта, антикорупційна політика, інституційна модель, НАБУ, НАЗК, внутрішній аудит, оперативно-розшукова діяльність, досудове розслідування.
Інституційна модель державного реагування на корисливі злочини у сфері вищої освіти